HISTOGENESIS AND MOLECULAR PECULIARITIES OF TERMINAL DUCT IN THE WOMAN'S MAMMARY GLANDS - Nikolenko, D.E. (Актуальні проблеми сучасної медицини: Вісник Української медичної стоматологічної академії, 2021)
The development of a woman's mammary glands occurs during the fertile age. It is during this period that the glands are subject to morpho-functional changes in the form of proliferation and differentiation of the epithelium in the parenchyma and elements of the stroma as response to the action of many stimulating physiological factors of the body. There changes have a tendency to be repeated several times during the woman's reproductive age. There is enough in-depth knowledge about the object of the cyclic effect of sex hormones in the woman's mammary glands. This study will expand knowledge about the important morphological state of the terminal ducts of the mammary glands before pregnancy and childbirth that can be of great importance in determining the histogenesis of possible pathomorphological changes in the gland of a dyshormonal and neoplastic nature. The aim of the study was to investigate the molecular characteristics of the parenchyma of the terminal ducts of the mammary glands of a non-pregnant woman of reproductive age. The study was carried out on autopsy material of 192 micro-incisions of breast tissue samples from 8 women who died of infectious diseases. Karyometry with the definition of the logarithm of the volume of the nuclei of the parenchymal elements in the structures of the terminal ducts was performed; histological, histochemical and immunohistochemical research methods were applied. The study identified histogenetic series of the epithelial lining in the parenchyma of the terminal ducts of the mammary gland; applying immunohistochemical markers enabled cytotyping of the epithelial elements of these ducts, as well revealing certain functions of the terminal ducts of the mammary glands before pregnancy and childbirth.